The Doubleday children's thesaurus - Bellamy, John, 1948-; Stevenson, Peter, 1953- (Garden City, N.Y. : Doubleday, 1987)
An illustrated thesaurus presenting over 6,000 word entries accompanied by synonyms, antonyms, and homonyms.
Keywords: English language -- Synonyms and antonyms -- Dictionaries, Juvenile; English language -- Synonyms and antonyms